Adverse Effects of Silver Diamine Fluoride Treatment among Preschool Children. (April 2018) - Duangthip, D.; Fung, M.H.T.; Wong, M.C.M.; Chu, C.H.; Lo, E.C.M.
This randomized clinical trial aimed to compare the adverse effects and parental satisfaction following the different regimes of silver diamine fluoride (SDF) treatment among preschool children. A total of 888 preschool children who had active dentin caries received different SDF application regimes: group 1, 12% SDF applied annually; group 2, 12% SDF applied semiannually; group 3, 38% SDF applied annually; and group 4, 38% SDF applied semiannually. Information on adverse effects—including tooth or gum pain, gum swelling, gum bleaching, and systemic toxicity—was collected through a parent-reported questionnaire within 1 wk after every SDF or placebo application. Information of parental satisfaction on children's dental appearance was collected at baseline and 30-mo examination. At the 30 mo, 799 children (90%) remained in the study. No acute systemic illness or major adverse effect was reported. No differences of all minor adverse effects among the 4 groups were found ( P > 0.05). Overall, prevalence of tooth and gum pain as perceived by patients and reported by parents was 6.6%, while gum swelling and gum bleaching were 2.8% and 4.7%, respectively. Blackening of carious lesions was common among all groups, with 36.7%, 49.5%, 65.6% and 76.3% in groups 1 to 4, respectively (χ 2 test, P < 0.001). The proportion of parents who were satisfied with their children's dental appearance in groups 1 to 4 was as follows: 67.6%, 61.5%, 70.8%, and 62.3%, respectively (χ 2 test, P > 0.05). Based on parental reporting, SDF does not cause acute systemic illness. Tooth or gum pain, gum swelling, and gum bleaching were uncommon and not significantly different among the study groups. Parental satisfaction with children's dental appearance was similar among all groups. The use of SDF following the study protocol for caries arrest is safe for preschool children. Collecting information on parental satisfaction and adverse effects is beneficial for dental professionals when deciding to adopt SDF treatment for preschool children (ClinicalTrials.gov NCT02385474).